Clinical factors associated with inappropriate prophylaxis of venous thromboembolic disease in critically ill patients. A single day cross-sectional study. Issue 143 (July 2016) - García-Olivares, Pablo; Guerrero, Jose Eugenio; Keough, Elena; Galdos, Pedro; Carriedo, Demetrio; Murillo, Francisco; Rivera, Antonio; ,
Abstract: Purpose: A poor implementation of VTE prophylactic measures recommended for critically ill patients has been observed in several epidemiological studies. The clinical factors associated with this have not been clearly established. The objective of our study was to identify which factors could be related to the inappropriate use of VTE prophylaxis. Methods: Analytic epidemiological study based on different aspects of VTE prophylaxis performed on Spanish ICU patients. A multiple logistic regression analysis was conducted to identify the risk factors associated with inappropriate prophylaxis, according to the American College of Chest Physicians 2012 guidelines. Results: We enrolled 777 patients. On admission, 62% presented medical, 30% surgical and 8% major trauma pathology. Of all patients, 41% were receiving an inappropriate prophylaxis, including 19% which did not receive any prophylaxis. The presence of a contraindication for pharmacological prophylaxis (OR 3.91, 95% CI 2.50–6.10) and non-medical pathology at ICU admission (OR 11.09; 95% CI 7.63–16.12) were associated with inappropriate prophylaxis. In contrast, mechanical ventilation (OR 0.70, 95% CI 0.45–0.98), bed rest > 48 h (OR 0.61, 95% CI 0.49–0.98), the use of a protocol for VTE prophylaxis (OR 0.66, 95% CI 0.45–0.98) and a VTE risk scoring system (OR 0.49, 95% CI 0.24–0.98) were associated with adequate prophylaxis. Conclusions: Our study highlighted a poor compliance with the VTE prophylaxis recommendations proposed for critical patients. The implementation of specific protocols for prophylaxis that include a correct evaluation according to VTE and haemorrhage risk, would allow for optimisation of mechanical and combined prophylaxis, improving adherence to the clinical practice guidelines. Highlights: VTE is an important healthcare and socio-economic problem due to its high morbidity and mortality. The use of VTE prophylaxis in ICU has shown to be effective, reducing its incidence. A poor implementation of VTE prophylaxis in ICU has been observed in epidemiological studies. According to guidelines, 41% of all patients were receiving an inappropriate prophylaxis. Correct evaluation of thrombotic and bleeding risk optimises mechanical and combined prophylaxis use. Implementation of prophylaxis protocols would improve adherence to clinical practice guidelines.